Preparation of a Sensor Based on Biomass Porous Carbon/Covalent-Organic Frame Composites for Pesticide Residues Detection - Liu, Yali; Zhou, Mingyue; Jin, Chen; Zeng, Jinxiang; Huang, Chao; Song, Qiuye; Song, Yonggui (Frontiers in Chemistry, 2020)
In this work, a covalent-organic framework with high carbon and nitrogen content microstructures (named COF-LZU1) assisted by 3D nitrogen-containing kenaf stem composites (represented as COF-LZU1/3D-KSCs) was constructed. Moreover, it was utilized for immobilizing acetylcholinesterase (AChE) for identifying trichlorfon a commonly applied organophosphorus (OP) pesticide. The development of COF-LZU1/3D-KSC was affirmed by SEM, PXRD, and EDXS. The findings confirmed that COF-LZU1 microstructures were uniformly developed on 3D-KSC holes by one-step synthesis approach, which can substantially enhance the eﬀective surface area. Also, the COF-LZU1/3D-KSC composite contains not only the nitrogen element in COF-LZU1 but also the nitrogen element in 3D-KSC, which will greatly improve the biocompatibility of the material. The AChE/COF-LZU1/3D-KSC integrated electrode was fabricated by directly fixing a large amount of AChE on the composite. At the same time, the integrated electrode has good detection efficiency for trichlorfon. Improved stabilization, wide-linear-range (0.2-19 ng/mL) and lower-detection limit (0.067 ng/mL) have been displayed by the sensor. Therefore, this sensor can be used as an important platform for the on-site detection of OP residues.